The chemical ecology of tropical forest diversity: Environmental variation, chemical similarity, herbivory, and richness. Issue 9 (12th July 2022) - Massad, Tara Joy; Richards, Lora A.; Philbin, Casey; Yamaguchi, Lydia Fumiko; Kato, Massuo J.; Jeffrey, Christopher S.; Oliveira, Celso; Ochsenrider, Kaitlin; de Moraes, Marcílio M.; Tepe, Eric J.; Cebrian‐Torrejon, Gerardo; Sandivo, McKenzie; et al.
Abstract: Species richness in tropical forests is correlated with other dimensions of diversity, including the diversity of plant–herbivore interactions and the phytochemical diversity that influences those interactions. Understanding the complexity of plant chemistry and the importance of phytochemical diversity for plant–insect interactions and overall forest richness has been enhanced significantly by the application of metabolomics to natural systems. The present work used proton nuclear magnetic resonance spectroscopy ( 1 H‐NMR) profiling of crude leaf extracts to study phytochemical similarity and diversity among Piper plants growing naturally in the Atlantic Rainforest of Brazil. Spectral profile similarity and chemical diversity were quantified to examine the relationship between metrics of phytochemical diversity, specialist and generalist herbivory, and understory plant richness. Herbivory increased with understory species richness, while generalist herbivory increased and specialist herbivory decreased with the diversity of Piper leaf material available. Specialist herbivory increased when conspecific host plants were more spectroscopically dissimilar. Spectral similarity was lower among individuals of common species, and they were also more spectrally diverse, indicating phytochemical diversity is beneficial to plants. Canopy openness and soil nutrients also influenced chemistry and herbivory. The complex relationships uncovered in this study add information to our growing understanding of the importance of phytochemical diversity for plant–insect interactions and tropical plant species richness.